Synthesis, Characterization, and Catalytic Properties of Metal–Polymer Complexes Based on Copolymers of Polyethylene(propylene) Glycol Maleates with Acrylic Acid - Burkeev, M. Zh.; Khamitova, T. O.; Havliček, D.; Sarsenbekova, A.Zh.; Davrenbekov, S.Zh.; Tazhbaev, E.M.; Kozhabekova, G.E.; Imanbekova, Zh.K.; Bolatbai, A.N. (Russian Journal of Applied Chemistry, 2019)
New mono- and bimetallic polymer nanocomposites based on polyethylene(propylene) glycol maleates with acrylic acid and silver and nickel metals were prepared and studied. Metal particles were immobilized into copolymer supports by reduction of Аg+ and Ni2+ ions from solution of their nitrates to Ag0 and Ni0 in the presence of a catalyst, a solution of silver chloride in aqueous ammonia. The structure and composition of the complexes were determined by spectroscopy, calorimetry, microscopy, and chromatography. The catalytic activity was studied using pyridine hydrogenation as a model reaction.
Keywords: polyethylene glycol maleate; polypropylene glycol maleate; catalysis; nanoparticles; metal–polymer complex; hydrogenation